SYMBOL OF WANDS IN J.K. ROWLING’S HARRY POTTER SERIES - Mirna Damayanti; Liliek Soelistyo (Institute of Research and Community Outreach - Petra Christian University, 2016)
This thesis examines the interpretations of Harry Potter’s and Voldemort’s wands which are related to the relationship between the wand and the owner. I am curious about finding the symbols behind the wands of Harry Potter and Lord Voldemort. The symbols that I use as the theory, reveal the power and the way they see the power through their wands. Therefore, the interpretations also reveal their relationships toward their wands. I interpret that both Harry’s and Voldemort’s wands disclose the personalities that they have. The relationship between the wands and the owner determines the success of each wizard to accomplish their goals. The affectionate relationship between Harry and his wand give mutual benefits for each of them. In contrast to Harry, Voldemort’s wand turns out to be a destructive weapon since there is no emotional attachment between him and his wand.